2023
DOI: 10.1037/aca0000423
|View full text |Cite
|
Sign up to set email alerts
|

Facial reactions to face representations in art: An electromyography study.

Abstract: Facial mimicry is a reaction to facial expressions. It plays a role in social interaction. Indeed, scholars associated facial mimicry with emotional contagion and understanding others' mental states such as intentions. This is the case for facial mimicry toward human facial expressions, but we know that facial expressions are widely depicted in art through face representations (visual creations that depict facial expressions). However, despite face representation involvement in social interactions, facial reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 67 publications
2
5
0
Order By: Relevance
“…This finding is consistent with the presence of a shared face-sensitive N170 component in processing real faces and faces depicted in art (e.g., Caharel et al, 2013; Jeffreys & Tukmachi, 1992, Rossion & Jacques, 2008; Sagiv & Bentin, 2001). Our results further corroborate with findings that face processing does not differ across art styles (Achour-Benallegue et al, 2016, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with the presence of a shared face-sensitive N170 component in processing real faces and faces depicted in art (e.g., Caharel et al, 2013; Jeffreys & Tukmachi, 1992, Rossion & Jacques, 2008; Sagiv & Bentin, 2001). Our results further corroborate with findings that face processing does not differ across art styles (Achour-Benallegue et al, 2016, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…face processing does not differ across art styles (Achour-Benallegue et al, 2016, 2021. Despite converging evidence pointing to the same mechanism underlying our perception of real faces and faces across different art styles, it is not clear whether faces in art are processed holistically, given the mixed results in the literature (George et al, 2005;Gold et al, 2012;Meinhardt-Injac et al, 2013;Pinna & Deiana, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…The observed facial mimicry toward facial icons may indicate the involvement of sensorimotor simulation in emotion processing when dealing with facial expressions that are inherently complex and ambiguous due to their nature as freely crafted artifacts. In light of the embodied emotion theory (refer to Box 3 in Supplementary materials ), the observed facial muscle reactions toward cross-cultural facial icons ( Achour-Benallegue et al, 2021 ) and stick figures ( Wessler and Hansen, 2021 ) provide substantial support to the simulated emotion we identified in our earlier study ( Achour-Benallegue et al, 2016 ). These findings further endorse our hypothesis regarding facial icons serving as indexes of emotions within the framework of the simulation theory.…”
Section: Beyond Art Agency: Experimental Psychology Approachsupporting
confidence: 70%
“…Stick figures not only triggered facial mimicry as much as did the photographs of real faces, but they also provided better material for recognizing emotions than photographs ( Wessler and Hansen, 2021 ). In a previous study ( Achour-Benallegue et al, 2021 ), we observed mimicry reactions, particularly of mouth expressions, in response to cross-cultural facial icons, suggesting that these icons might enhance a simulation process through sensorimotor reactions. In this study, mimicry reactions to the upper part of facial icons were challenging to observe, but findings on the effect of valence on muscle reactions suggested a possible tendency of mimicry reactions in the corrugator (activation of the corrugator muscle was observed in response to negative valence, while relaxation of the corrugator occurred in response to positive valence, accompanied by increased zygomaticus activity in positive valence conditions; however, in positive valence condition, the presentation of a strong-corrugator expression in facial icons impeded participants’ zygomaticus activation).…”
Section: Beyond Art Agency: Experimental Psychology Approachmentioning
confidence: 65%
“…Therefore, Hess considered that spontaneous facial mimicry was not a necessary precondition for emotional contagion, and (despite frequent co-occurrences) spontaneous facial mimicry and emotion contagion do not necessarily co-occur [22]. However, some studies showed supporting evidence for the link between spontaneous facial mimicry and emotional contagion under an affiliative social context [35][36][37] Based on the tenets of organizational psychology and the appraisal theories of emotion [38], the Elfenbein "affective process theory" (APT) [30] emphasized the roles played by social appraisal and comparison, emotional interpretation, and empathy, in terms of emotional contagion.…”
Section: Spontaneous Facial Mimicry and Emotional Contagionmentioning
confidence: 99%